Optimum transmitter current distribution for dynamic wireless power transfer with segmented array - Jayathurathnage, Prasad Kumara Sampath (2020)
The misalignment problem is a major challenge in dynamic wireless power transfer systems with a segmented transmitter (Tx) array. Tx coils farther away from receiver (Rx) experience higher currents as compared to Tx coils nearer to Rx coil leading to higher losses and lower performances. This paper reports theoretical optimum current distribution among Tx coils for any Rx position. A current amplitude modulation scheme is analyzed with the analogy of N-Cartesian coordinate equivalent of spherical coordinates. Efficiency and transferred power are evaluated for the proposed current distribution, and further optimization is performed with respect to load resistance, operating frequency, and the number of simultaneously powered Tx coils. The maximum performances that can be obtained with the optimized design conditions have been derived as well. The analysis is validated using numerical and experimental results.